Analysis of Standard Precautions and Prevention of Nosocomial Infections in Improving Patient Safety Culture Among Nurses at Duta Indah Hospital, Jakarta - N. Siti Nuraeni; Bayu Wahyudi; Yuniati Lestari (CV. Civiliza Publishing, 2025)
Patient safety is a top priority in healthcare, yet healthcare-associated infections (HAIs) remain a persistent challenge. Duta Indah Hospital Jakarta experiences gaps between infection prevention standards and actual nursing practices, affecting its patient safety culture. To analyze nurses’ understanding and implementation of standard precautions and HAI prevention, examine their contribution to patient safety culture, and identify influencing factors. A qualitative case study was conducted through in-depth interviews with 17 informants, observations, and document review. Data were analyzed thematically. Standard precautions were acknowledged as the foundation of infection prevention but were not optimally applied, especially in preventing ventilator-associated pneumonia (VAP). Nurses supported patient safety culture through hand hygiene compliance, proper use of personal protective equipment (PPE), environmental hygiene, and HAI bundles. Barriers included unsupportive mindsets and work culture, limited PPE and hand hygiene facilities, and high workload. Standard precautions are vital in preventing HAIs and fostering a patient safety culture. Strengthening their implementation requires education, compliance monitoring, and managerial support. Adherence to national regulations Law No. 17/2023 on Health, Minister of Health Regulation No. 27/2017 on Infection Prevention and Control, and Minister of Health Regulation No. 11/2017 on Patient Safety is essential as a legal framework to reinforce patient safety culture in hospitals.